Medial and Lateral Posterior Tibial Slope Are Independent Risk Factors for Noncontact ACL Injury in Both Men and Women. Issue 8 (9th August 2021) - Hohmann, Erik; Tetsworth, Kevin; Glatt, Vaida; Ngcelwane, Mthunzi; Keough, Natalie
Background: Higher posterior tibial slope (PTS) is a risk factor for anterior cruciate ligament (ACL) injury in men and women. The individual contribution of the lateral (LPTS) and medial (MPTS) slope has not yet been investigated. Purpose: To determine whether either the LPTS or the MPTS is an independent risk factor for ACL injury, and to determine sex-specific differences between patients with ACL-deficient and ACL-intact knees. Study Design: Cohort study; Level of evidence, 3. Methods: We reviewed knee magnetic resonance (MR) images performed on ACL-deficient and ACL-intact knees between January 2018 and June 2020 at a single institution. Inclusion criteria were isolated ACL injury and noncontact mechanism (ACL-deficient group) and nonspecific knee pain and no history of injury (ACL-intact group). Exclusion criteria for both groups were the following: previous knee surgery; meniscal, collateral ligament, posterior cruciate ligament, or multiligamentous injuries; radiological evidence of osteoarthritis; and chondral damage on the tibia. The MR images were used to establish the posterior bony slope at 25%, 50%, and 75% from the medial and/or lateral border of the tibial plateau with respect to the proximal tibial anatomic axis. One-way analysis of variance (ANOVA) was used to determine differences in PTS at the 25%, 50%, and 75% distances for the medial and lateral tibial plateau between the groups and between the sexes. Results: Overall, 325 images were included (mean age, 36.1 ± 11.1 years; 142 ACL-deficient images [82 men and 60 women]; 183 ACL-intact images [112 men and 71 women]). MPTS and LPTS were significantly higher at 25%, 50%, and 75% in the ACL-deficient group (range, –2.7° to –5.7°) compared with the ACL-intact group (range, –2.1° to 1.5°; P = .00001). Similarly, MPTS and LPTS were significantly different in men versus women ( P = .00001). ANOVA revealed that there were no significant differences in PTS between men and women for all measures (MPTS, LPTS, ACL-deficient, ACL-intact; P = .68). Conclusion: The study results demonstrated that higher MPTS and LPTS is a potential risk factor for ACL injury in both men and women. However, despite being highly statistically significant, the differences between groups and sexes were small and may not be clinically relevant.